Caracterización de la función de las enzimas Ten Eleven Translocation (TETs) humanas en la desmetilación del DNA inducida por altos niveles de glucosa (2018)
Introduction The process of DNA demethylation was found necessary for various processes, for example, the maturation of gametes and zygote. However, the underlying mechanisms to the demethylation were not known and for a long time a passive mechanism, due to lack of maintenance, was considered as the only possible pathway. Recently, it has been discovered that members of TET (Ten-Eleven-Translocation) family are involved in active demethylation pathway. Despite that the mechanism used by enzymes TET is an oxidative process, the oxidation has not been considered as a mechanism that could be related with epigenetic changes in DNA demethylation and methylation observed in complex diseases, such as Diabetes Mellitus characterized by oxidative stress. Methodology iRNAs were designed for each one of TET enzymes (TET1, TET2 and TET3), which were cloned in an expression vector (pGeneClip Vector) and transformed in competent cells with pGeneClip Vectors containing the iRNA. Once the sequence was confirmed...